Rozwój stacjonarnej bankowości telefonicznej w Polsce - Solarz, Małgorzata (The Development of Stationary Telephone Banking in Poland, 2006)
A stationary telephone plays an important role in banking as the basis of phone banking. The core aspect of this fully automated service is 24 hour, remote access to the client's bank accounts by means of a telephone, as well as obtaining, in this way, information regarding bank's offers. In Poland phone banking emerged in 1996, however the phone as a distribution channel was used in banks much earlier, mainly for information and promotion purposes. As time went by it became more and more functional. In July 2003 banks' clients in Poland may take advantage of 28 automated, telephone services (8 info-lines and 20 tele-services) offered by 20 banking institutions. Such development of telephone banking is supported by a rapidly increasing number of banking transactions conducted by means of tele-services, which in 2003 amounted to over 1.1 million transactions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 227-237